Rhizospheric actinomycetes from turmeric (Curcuma longa L.): Isolation, detection of the biosynthetic gene clusters, and anticancer activity against T47D cancer cells - Aniska Novita Sari, Dini Achnafani, Mery Budiarti, Sari Haryanti, Harto Widodo, Nastiti Wijayanti, Endah Retnaningrum (Journal of Applied Pharmaceutical Science, 2025)
This study investigates actinomycete bacteria in the rhizosphere of turmeric rhizomes, which can produce bioactive compounds like their host, particularly those with anticancer properties. The main goals were to isolate these bacteria, analyze their biosynthetic gene clusters (BGCs), and test their effects on T47D cancer cells. We identified seven isolates, revealing three BGC combinations of PKS1, PKS2, and non-ribosomal peptide synthetase. Notably, isolate TC-ARCL7, which had both PKS1 and PKS2 genes, demonstrated significant anticancer activity against T47D cells, with an IC50 of 0.2 μg/ml, much more potent than Doxorubicin (7.9 μg/ml), curcumin (23.13 μg/ ml), and turmeric ethanol extract (50 μg/ml). This isolate was closely related to Kitasatospora misakiensis or Kitasatospora purpeofusca, with 99.08% sequence similarity. The findings highlight that similar BGCs do not always correlate with anticancer activity and suggest the potential for developing new pharmaceutical compounds.
Keywords: Actinomycetes rhizosphere, Curcuma longa L., NRPS, PKS1, PKS2, T47D